Do Job Characteristics Affect an Individual's Performance? - Wirastuti, Wiri; Buntuang, Pricylia; Risnawati, Risnawati; Nurjannah, Nurjannah (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to determine whether job characteristics affect the performance of an employee. This research is designed using a quantitative approach with the purpose of seeing the influence, causal relationship between the variables studied. The population of this study were Central Yamaha Palu employees totalling 44 respondents. The determination of this research sample was determined by the census technique, so that the entire population was used as a research sample. This research data collection includes observation and questionnaires. The data analysis technique of this research is descriptive statistics and simple linear regression. Based on the results of the descriptive statistic and simple regression analysis conducted, there is a positive and significant influence of job characteristics on the performance is 55% of Central Yamaha Palu employees.